Strangulating obstruction of the small intestine by a fibrous band originating on the nephrosplenic ligament. (13th November 2019) - Gandini, M.; Labate, F.; Rosso, A.; Giusto, G.
Summary: During a laparotomy for colic signs in a 2‐year‐old male Thoroughbred, a portion of approximately 7 m of the jejunum was found entrapped in a fibrous band originating from the nephrosplenic ligament. The entrapped jejunum was necrotic and was removed. Two months after the first surgery, a laparoscopy was performed to close the nephrosplenic space and it was possible to identify several fibrous bands bridging from the renal capsule to the splenic capsule and a fibrotic plate over the spleen. This is the first report of a strangulating obstruction of the jejunum in the nephrosplenic space and of fibrous bands bridging from the nephrosplenic ligament to the spleen. The fibrous bands were likely due to inflammation caused by previous, multiple left dorsal displacements of the bowel, which resolved spontaneously.